Postoperative Pain Comparison Between Open Hemorrhoidectomy and Stapled Hemorrhoidopexy on Internal Hemorrhoid at Siloam Hospitals Lippo Village - Taufik Sudirman; Alvin Wiguna (Medicinus, 2022)
Background: Hemorrhoids have a prevalence of 4,4%. Surgery is one of the modalities for treating hemorrrhoids. The method accepted as the "golden standard" is open hemorrhoidectomy. Although considered effective, open hemorrhoidectomy is still often associated with a significant rate of morbidity and pain symptoms that are a complaint of most patients. Therefore, another method is an alternative, namely, stapled hemorrhoidopexy. Some studies showed that stapled hemorrhoidopexy has a lower occurrence of postoperative pain, and others offer the opposite.Methods: This study was conducted at Siloam Hospitals Lippo Village between February and March 2019. Samples were taken as many as 70 patients by taking secondary data from medical records. Patients diagnosed with third or fourth degree hemorrhoids and undergoing open hemorrhoidectomy or stapled hemorrhoidopexy will be taken the pain score from the visual analogue scale. Data is then tabulated using Microsoft Excel and analysed using SPSS.Result: the occurrence of postoperative pain in the stapled hemorrhoidopexy and open hemorrhoidectomy group, respectively, are 80% and 97%, with a p-value of 0,055. The average visual analogue scale score for open hemorrhoidectomy and stapled hemorrhoidopexy was 3±1,39 and 2±1,39, respectively, with a p-value of 0.003.Conclusions: the result showed that the occurrence of postoperative pain was not statistically significant. And the average visual analogue scale score was lower in the stapled hemorrhoidopexy group.